Willingness to pay for the consumption of green food product among households - Md Jusoh, Zuroni; Ahmat, Nizam (Malaysian Consumer and Family Economics Association, 2017)
Green food refers to food that is safe to eat, good quality, healthy, concerned about animal welfare and is produced under the principles of sustainable development. The objective of this study is to determine the ability of households to pay according to the attributes of green food product, and to estimate the implicit price for each attribute that is modelled. Data collection was carried out in the Klang Valley from June until August 2016 by using convenient sampling method. A total of 309 respondents were selected. Data were collected using questionnaires distributed to households in the Klang Valley area, namely the Federal Territory of Kuala Lumpur, Putrajaya, Ampang and Subang Jaya. Data were analysed using SPSS version 21 for descriptive and inferential test while SAS and 9.0 LIMDEP logit 3.0 was used to analyse the household’s willingness to pay (WTP) through the Choice Model (CM) technique. The study found that on average, consumers are willing to pay RM3.46 for the reduction of risk to human health and willing to accept the compensation of RM1.723 for the environmental impact of the chicken production process. It explains that on average, households would be very concerned about the risk factors to human health and the impact on the environment in green food choices for a healthy lifestyle. Meanwhile, the external characteristic was not significant and did not affect households in sustainable food choices. Therefore, the food manufacturers and the government should take the initiative to apply these attributes in sustainable food production so that a healthy lifestyle can continue to be practised by the consumers.